The Origins of Urban Rational Behavior - Gerardi, Steven (Advances in Social Sciences Research Journal, 2021)
This effort will examine the roots of Urban Rationalization based on Georg Simmel, Max Weber, Burgess and Park’s urban Classical Sociological Theories.